2015
DOI: 10.1089/tmj.2014.0028
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations Service for Chronic Disease Patient in Multimodel Sensors Home Environment

Abstract: With advanced technologies in hand, there exist potential applications and services built around monitoring activities of daily living (ADL) of elderly people at nursing homes. Most of the elderly people in these facilities are suffering from different chronic diseases such as dementia. Existing technologies are mainly focusing on non-medication interventions and monitoring of ADL for addressing loss of autonomy or well-being. Monitoring and managing ADL related to cognitive behaviors for non-medication interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Wearable sensors are used to acquire data to generate these activity patterns. A similar system is proposed in [ 40 ]. Suryadevara et al [ 41 ] develop an intelligent home monitoring system to detect behavior changes and forecast the behavior of elderly people.…”
Section: Smart Home Projects and Applicationsmentioning
confidence: 99%
“…Wearable sensors are used to acquire data to generate these activity patterns. A similar system is proposed in [ 40 ]. Suryadevara et al [ 41 ] develop an intelligent home monitoring system to detect behavior changes and forecast the behavior of elderly people.…”
Section: Smart Home Projects and Applicationsmentioning
confidence: 99%
“…A combination of clinical recommendations and the involvement of physicians with intelligent health monitoring systems for the elderly can improve patient safety. 21 A chronic disease care system could improve treatment continuity for adults with type 2 diabetes mellitus. 13 Additionally, Gokalp and Clarke 22 found that most of the existing monitoring systems could provide smart life services such as meal preparation, personal hygiene, bathing, and dressing.…”
Section: Discussionmentioning
confidence: 99%
“…There already are proposals for solutions, e.g. multi-model sensor-based home environment for demented people [49]. However, so far there are only few if any research on solutions that are designed for multi-disease domain, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%